Surveillance and Monitoring the Cereal Rust Diseases in Lebanon, Morocco and Tunisia in 2024 - Nazari, Kumarse; El Amil, Rola; Al-Jaboobi, Muamar; Maafa, Ilyass; Kemal, Seid Ahmed; Ramdani, Abdelhamid; Ibriz, Hafid; SBAI, Ibtihel; Ramdhane, Nasraoui; Abdsattar, Bouslimi (International Center for Agricultural Research in the Dry Areas, 2024)
Achieving durable resistance to wheat rust disease and effectively managing it requires continuous monitoring of pathogen movement and analyzing their pathogenic variations. Despite the severe drought in wheat-growing areas across CWANA in 2024, the Regional Cereal Rust Research Center in Turkey, along with national rust surveillance teams, conducted rust monitoring in Morocco, and the rust surveys in Lebanon and Tunisia were conducted by the national rust survey teams, adhering to BGRI surveillance guidelines. Surveillance data were collected from 35, 64, and 27 locations in Lebanon, Morocco, and Tunisia, respectively. The ODK rust survy mobile application was use during the rust survey in Morocco, National teams from the Lebanese Agricultural Research Institute, Morocco's Institut National de la Recherche Agronomique, and Tunisia's INSTITUT NATIONAL DES GRANDES CULTURES carried out rust surveys in wheat-producing regions. They recorded GPS coordinates, rust disease status, and crop phenology, then shared this data with the online Global Cereal Rust Surveillance and Monitoring System in accordance with BGRI's standard protocol